Cumulative directional calcium gluing between phosphate and silicate: A facile, robust and biocompatible strategy for siRNA delivery by amine-free non-positive vector. (July 2019) - Choi, Eunshil; Lee, Juyong; Kwon, Ick Chan; Lim, Dong-Kwon; Kim, Sehoon
Abstract: For siRNA therapeutics, the use of positively charged amine-rich delivery vectors has been indispensable, but the amine-associated toxicological responses remain a clinical conundrum. Herein, we report a new strategy of harnessing a biocompatible, biodegradable and well-tolerated nanomaterial as an amine-free non-positive carrier for siRNA delivery. By employing mesoporous silica nanoparticles (MSNs) as a biocompatible vector, siRNA is loaded nonconventionally through calcium ion (Ca 2+ )-mediated interconnection (calcium gluing) between phosphates of siRNA and surface silicates of MSNs in a sequential, cumulative and directional way. The "one-pot" gluing process utilizing endogenously abundant Ca 2+ ions offers a simple but robust means of siRNA loading on the non-positive bare surface of MSNs without the aid of multi-amine functionalization, and thus minimizes the risk of amine-associated cytotoxicity and immunogenicity while keeping the intrinsic biocompatibility of MSNs. As demonstrated with loading of an anticancer siRNA, this strategy allows stable in vivo delivery of siRNA for targeted gene silencing, and capitalizes on the unique structural versatility of MSNs by simultaneously delivering a pore-loaded chemodrug to synergistically enhance the treatment efficacy. Therefore, the Ca 2+ -glued MSNs as a general siRNA carrier platform provide a less toxic, less laborious and more utilitarian delivery tool for more effective and safer siRNA therapeutics. Graphical abstract: Image 1